Cluster approach to formation of nitrogen–rare gas cryoalloys - Solodovnik, A.A.; Danchuk, V.V.; Mysko, N.S. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
Structure of solid binary N2–Kr and N2–Ar solutions were studied by transmission electron diffraction (THEED). The samples were prepared in situ by deposition of gaseous mixture onto an Al substrate cooled to 20 K. The lattice parameters for low concentrations of one of the components were measured. The relative change of the lattice parameter per unit concentration is determined for N2 impurity in Kr and Ar as well as for Kr and Ar in N2. Analysis of the concentration dependence of the lattice parameters for low fractions of both components was performed within a cluster model in the three-particle approximation.